Critical research needs for identifying future changes in Gulf coral reef ecosystems - Feary, David (2013)
Expert opinion was assessed to identify current knowledge gaps in determining future changes in Arabian/Persian Gulf (thereafter ‘Gulf’) coral reefs. Thirty-one participants submitted 71 research questions that were peer-assessed in terms of scientific importance (i.e., filled a knowledge gap and was a research priority) and efficiency in resource use (i.e., was highly feasible and ecologically broad). Ten research questions, in six major research areas, were highly important for both understanding Gulf coral reef ecosystems and also an efficient use of limited research resources. These questions mirrored global evaluations of the importance of understanding and evaluating biodiversity, determining the potential impacts of climate change, the role of anthropogenic impacts in structuring coral reef communities, and economically evaluating coral reef communities. These questions provide guidance for future research on coral reef ecosystems within the Gulf, and enhance the potential for assessment and management of future changes in this globally significant region.